Endothelial Cell Seeding on Crosslinked Collagen: Effects of Crosslinking on Endothelial Cell Proliferation and Functional Parameters - Wissink, M. J. B.; van Luyn, M. J. A.; Beernink, R.; Dijk, F.; Poot, A. A.; Engbers, G. H. M.; Beugeling, T.; van Aken, W. G.; Feijen, J. (Thrombosis and Haemostasis, 2000)
Endothelial cell seeding, a promising method to improve the performance of small-diameter vascular grafts, requires a suitable substrate, such as crosslinked collagen. Commonly used crosslinking agents such as glutaraldehyde and formaldehyde cause, however, cytotoxic reactions and thereby hamper endothelialization of currently available collagen-coated vascular graft materials.The aim of this study was to investigate the effects of an alternative method for crosslinking of collagen, using N-(3-dimethylaminopropyl)-N’-ethylcarbodiimide (EDC) in combination with N-hydroxysuccinimide (NHS), on various cellular functions of human umbilical vein endothelial cells (HUVECs) in vitro. Compared to non-crosslinked type I collagen, proliferation of seeded endothelial cells was significantly increased on EDC/NHS-crosslinked collagen. Furthermore, higher cell numbers were found with increasing crosslink densities. Neither the morphology of the cells nor the secretion of prostacyclin (PGI2), von Willebrand factor (vWF), tissue plasminogen activator (t-PA) and plasminogen activator inhibitor (PAI-1) was affected by the crosslink density of the collagen substrate. Therefore, EDC/NHScrosslinked collagen is candidate substrate for in vivo application such as endothelial cell seeding of collagen-coated vascular grafts.
Keywords: Vascular grafts; collagen crosslinking; endothelial cell seeding; endothelial cell function